2013
DOI: 10.1155/2013/154919
|View full text |Cite
|
Sign up to set email alerts
|

Effect ofEx VivoCulture Conditions on Immunosuppression by Human Mesenchymal Stem Cells

Abstract: A microarray analysis was performed to investigate whether ex vivo culture conditions affect the characteristics of MSCs. Gene expression profiles were mainly influenced by the level of cell confluence rather than initial seeding density. The analysis showed that 276 genes were upregulated and 230 genes downregulated in MSCs harvested at ~90% versus ~50% confluence (P < 0.05, FC > 2). The genes that were highly expressed in MSCs largely corresponded to chemotaxis, inflammation, and immune responses, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
2
14
0
Order By: Relevance
“…Although specific production of these factors appears to be lower throughout cultivation under stirred conditions when compared to static cultures handled with the same feeding scheme, ASC cultures showed a considerable increase in specific production rates of both IL‐6 and VEGF by the end of culture (seven days). This is in line with recent findings indicating that during cell growth MSC show up‐regulation of proliferation‐related genes, while several cytokines and growth factor genes involved in immunosuppression and reconstitution of damaged tissues are up‐regulated in MSC harvested at higher confluence (including IL‐6 and VEGFA) [41, 42]. Thus, we can speculate that a longer stationary phase in ASC cultures may have triggered the up‐regulation of these genes.…”
Section: Discussionsupporting
confidence: 91%
“…Although specific production of these factors appears to be lower throughout cultivation under stirred conditions when compared to static cultures handled with the same feeding scheme, ASC cultures showed a considerable increase in specific production rates of both IL‐6 and VEGF by the end of culture (seven days). This is in line with recent findings indicating that during cell growth MSC show up‐regulation of proliferation‐related genes, while several cytokines and growth factor genes involved in immunosuppression and reconstitution of damaged tissues are up‐regulated in MSC harvested at higher confluence (including IL‐6 and VEGFA) [41, 42]. Thus, we can speculate that a longer stationary phase in ASC cultures may have triggered the up‐regulation of these genes.…”
Section: Discussionsupporting
confidence: 91%
“…Principle Component Analysis (PCA) using these genes separated the samples into 2 groups, one included 50% confluent BMSCs, while the other included 80% and 100% confluent BMSC (Figure 5A). These results were consistent with published data that BMSCs of high confluence have different gene expression profiles compared to those of low confluence 52 . We then identified 2708 genes that were differentially expressed among the 3 confluences by using 2-way ANOVA (p-value <0.001).…”
Section: Resultssupporting
confidence: 93%
“…It has been showed that growth factors such as HGF can decrease the rate of MSCs proliferation [34]. Moreover, initial plating density can affect the genes regulating cell proliferation [35].…”
Section: Discussionmentioning
confidence: 99%